(untitled) (American Journal of Arts and Human Science, 2022)
President Rodrigo Roa Duterte’s discourse is somehow different from the past presidents that governed the country. Consequently, this made him the most controversial and misunderstood politician for his language. Since metaphors form a significant part of the discourses, this study aims at examining the metaphors used by President Duterte and their possible ideological repercussions to people from different walks of life. The corpora of this study were ten transcripts of his political speeches from the period of his presidential campaign and the early period of his presidency. The identification of metaphorical expressions in ten texts was conducted using a method based on the conceptual metaphor themes listed by Lesz (2011) and were analyzed in the framework of Cognitive Metaphor Theory by Lakoff and Johnson (1980). The analysis showed that there were diverse conceptual metaphors identified in the speeches of the president and the employment in his speeches allows him to create associations between unrelated concepts like people, objects, or ideas. Thus, his audience can use their imaginations in order to integrate their understanding. Moreover, it was found out that the employment of other elements of language was also present. It is therefore recommended to analyze these elements to better understand his identity, ideologies, and role as the country’s president as this may fairly address the gap among the conceptual domains of people living in Luzon, Visayas and Mindanao